Description of two new species of Telegeusis, including the first species of Telegeusinae from Guatemala (Coleoptera: Omethidae) - López-Pérez, Sara; Zaragoza-Caballero, Santiago (Zootaxa, 2026)
Two new species of Telegeusinae are described and illustrated. One species is recorded in Valle de Bravo, Mexico, and the second is the first species of the subfamily to be recorded in Guatemala. Moreover, we propose Platyphalus López-Pérez and Zaragoza-Caballero as a replacement name of Platydrilus López-Pérez and Zaragoza-Caballero, 2021 which is a junior homonym of Platydrilus Michaelsen, 1891 (Annelida: Oligochaeta: Eudrilidae), and therefore a pre-occupied name, Platyphalus magaliae (López-Pérez and Zaragoza-Caballero, 2021) is proposed as a new combination.